CEGAH NYERI LEHER SEJAK USIA DINI: INTERVENSI EDUKASI GAYA HIDUP SEHAT DI PANTI ASUHAN BANUA BERKAH MANDIRI - Ridhani, Akhmad; Saputri, Juliani; Wicaksono, Utomo; Hasanah, Uswatun; Prayogo, Dadan; Anggelina, Denastasia Deswita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Neck pain is a musculoskeletal complaint that often occurs in adolescents, especially due to poor posture and excessive use of electronic devices. This condition has an impact on quality of life, including decreased productivity and psychological well-being. This community service activity aims to improve adolescents' knowledge and skills in preventing neck pain from an early age through healthy lifestyle education. The implementation method consists of interactive lectures, demonstrations, and redemonstrations of simple postural exercises, which will be held on December 11, 2024 at the Banua Berkah Mandiri Orphanage, Banjarmasin. The activity was attended by 22 teenagers with an age range of 10–17 years. The results of the evaluation showed a significant increase: before education, most participants were in the